An In Vitro Corrosion Study of Open Cell Iron Structures with PEG Coating for Bone Replacement Applications - Lucia Haverová; Renáta Oriňaková; Andrej Oriňak; Radka Gorejová; Matej Baláž; Petr Vanýsek; Miriam Kupková; Monika Hrubovčáková; Pavol Mudroň; Jozef Radoňák; Zuzana Orságová Králová; Andrea Morovská Turoňová (Metals, 2018)
Iron-based substrates with polyethylene glycol coating were prepared as possible materials for biodegradable orthopedic implants. Biodegradable materials that provide mechanical support of the diseased tissue at the time of implanting and then disappear gradually during the healing process are sometimes favored instead of permanent implants. The implant degradation rate should match the time of the tissue regrowth. In this work, the degradation behavior of iron-based foams was studied electrochemically during immersion tests in Hanks’ solution. The corrosion rate of the polyethylene glycol-coated samples increased and the corrosion potential shifted to more negative values. This indicates an enhanced degradation rate as compared to the uncoated material, fulfilling the goal of being able to tune the degradation rate. It is the interfacial interaction between the hydrophilic polymer layer and the iron surface that is responsible for the enhanced oxidation rate of iron.